E D U K A S I T E N T A N G TEKNIK MASSAGE COUNTER PRESSURE TERHADAP PENGURANGAN RASA NYERI PERSALINAN KALA I - Kristin Natalia; Weni Damayanti; Vitrilina Hutabarat (INSTITUT KESEHATAN DELI HUSADA, 2021)
Labor pain is a physiological condition that is generally experienced by almost all women who give birth. Pain comes from uterine contractions and cervical dilation. With the increasing frequency of uterine contractions, the pain felt by the mother in childbirth will be even stronger. This education aims to increase the knowledge and insight of mothers about how to use counter pre ssure massage techniques to reduce the pain of childbirth during the first stage of labor. This education uses an approach approach to mothers in labor so that they can perform counter pressure massage techniques during the first stage of labor. This massage technique is carried out for 20 minutes during contractions. The targets in this education are 1st stage mothers. This counseling technique starts from identifying the first stage mothers, preparing places and targets, preparing materials, extension tools and implementing teams. This education was carried out at the Kurnia Independent Practice Midwives, Deli Tua District. The results of this counseling indicate that by applying a counter pressure massage technique on the mother's waist can reduce labor pain from mothers who experience moderate pain to mild pain and mothers who experience severe pain to moderate pain p value = 0.007 (p. <0.05). It can be concluded that there is a significant effect of the application of counter pressure massage techniques on reducing pain in stage I labor. It is recommended that mothers who give birth during stage I are able to do this technique of counter pressure massage correctly.